Neurosyphilis Presenting as Sleep Disorder and Muscle Soreness Complicated With HIV Infection: A Case Report - Shu-Qi Yang; Hua-Tang Zhang; Yi-Jie Lin; Xing Wang; Yan-Yan Qiu; Xue-Ping Yu (Case Reports in Infectious Diseases)
Neurosyphilis is a tertiary syphilis complication or manifestation caused by Treponema pallidum, which invades the central nervous system. Its clinical manifestations are often nonspecific. Neurosyphilis symptoms frequently resemble those of spinal cord diseases and mental disorders, posing significant challenges for early diagnosis. With improving living standards and unprotected sexual behaviors becoming more common, the global incidence of syphilis has increased, along with a concurrent rise in reports of neurosyphilis, particularly among individuals with HIV infection. Although some patients with neurosyphilis mainly present with brain-related symptoms, it is rare for sleep disorders and general muscle soreness to be the predominant manifestations. This paper presents a case of neurosyphilis complicated by HIV coinfection, manifesting as sleep disorder and muscle soreness, providing insight into the impact of syphilis infection on the nervous system.